Morphology-density relation, quenching, and mergers in CARLA clusters and protoclusters at 1.4 < z < 2.8 - Mei, Simona; Hatch, Nina A.; Amodeo, Stefania; Afanasiev, Anton V.; Breuck, Carlos De; Stern, Daniel; Cooke, Elizabeth A.; Gonzalez, Anthony H.; Noirot, Gaël; Rettura, Alessandro; Seymour, Nick; Stanford, Spencer A.; et al. (Astronomy and astrophysics, 2023)
At redshifts of z ≲ 1.3, early-type galaxies (ETGs) and passive galaxies are mainly found in dense environments, such as galaxy clusters. However, it remains unclear whether these well-known morphology-density and passive-density relations have already been established at higher redshifts. To address this question, we performed an in-depth study of galaxies in 16 spectroscopically confirmed clusters at 1.3 < z < 2.8 from the Clusters Around Radio-Loud AGN (CARLA) survey. Our clusters span a total stellar mass in the range of (approximate halo mass in the range of ). Our main finding is that the morphology-density and passive-density relations are already in place at z ∼ 2. The cluster at z = 2.8 shows a similar fraction of ETG as in the other clusters in its densest region, however, only one cluster does not provide enough statistics to confirm that the morphology-density relation is already in place at z ∼ 3. The cluster ETG and passive fractions depend mainly on local environment and only slightly on galaxy mass; also, they do not depend on the global environment. At lower local densities, where ΣN < 700 gal/Mpc2, the CARLA clusters exhibit a similar ETG fraction as the field, in contradiction to clusters at z = 1, which already exhibit higher ETG fractions. This implies that the densest regions influence the morphology of galaxies first, with lower density local environments either taking longer or only influencing galaxy morphology at later cosmological times. Interestingly, we find evidence of high merger fractions in our clusters with respect to the CANDELS fields, but the merger fractions do not significantly depend on local environment. This suggests that merger remnants in the lowest density regions can reform disks fueled by cold gas flows, but those in the highest density regions are cut off from the gas supply and will become passive ETGs. The percentages of active ETGs, with respect to the total ETG population, are 21 ± 6% and 59 ± 14% at 1.35 < z < 1.65 and 1.65 < z < 2.05, respectively, and about half of them are mergers or asymmetric in both redshift bins. All the spectroscopically confirmed CARLA clusters have properties that are consistent with clusters and proto-clusters, confirming that radio-loud active galactic nuclei are lighthouses for dense environments. The differences between our results and other findings that point to enhanced star formation and starbursts in cluster cores at similar redshifts are probably due to differences in the sample selection criteria; for example, selection of different environments hosting galaxies with different accretion and pre-processing histories.
Gesehen am 03.05.2023